VALIDATED STABILITY-INDICATING HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR THE ESTIMATION OF TORSEMIDE - KV, LALITHA; RAVEENDRA REDDY J; DEVANNA N (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This assessment depicts the strength of exhibiting reverse-phase high performance liquid chromatography (RP-HPLC) method for the estimation of torsemide in pharmaceutical estimation structures. Methods: In the present work, total protein-HPLC technique has been produced for the estimation of torsemide active pharmaceutical ingredient (API). Constrained degradation HPLC strategy was created with versatile mobile phase of methanol:water in the proportion of 90:10 v/v. The stream pace of 1 ml/min was utilized on Inertsil ODS 3V segment (250 mm×4.6 mm, 5 μm molecule size). Results: The retention time of torsemide was seen at 8.267 min, method was validated for all validation parameters as per the International Council for Harmonization guidelines. The linearity range was 10–60 μg/ml, correlation coefficient was 0.9993, and percentage relative standard deviation in the precision studies was <2%, with percentage recovery 100.56–101.03 (within acceptable range of 98–102%). The assay result was found to be 100.88% (i.e., within 95–105%), passes the specifications for robustness parameters. Limit of detection of torsemide was found to be 0.0162 μg/ml and limit of quantitation of torsemide was found to be 0.0534 μg/ml. Conclusion: The medication was exceptionally delicate to antacid pursued by at risk to corrosive, photolytic, warm, and oxidative conditions. The created and approved method showing HPLC technique is observed to be direct, exact, precise, explicit, and powerful. Henceforth, the technique can be utilized routinely for the estimation of torsemide API.